How close is your government to its people? Worldwide indicators on localization and decentralization - Maksym Ivanyna; Anwar Shah (Kiel Institute for the World Economy (IfW), 2013)
This paper is intended to provide an assessment of the impact of the silent revolution (decentralization reforms) of the last three decades on moving governments closer to people to establish fair, accountable, incorruptible and responsive governance. To accomplish this, a unique data set is constructed for 182 countries by compiling data from a wide variety of sources to examine success toward decentralized decision making across the globe. An important feature of this data set is that, for comparative purposes, it measures government decision making at the local level rather than at the sub-national levels used in the existing literature. The data are used to rank countries on political, fiscal and administrative dimensions of decentralization and localization. These sub-indexes are aggregated and adjusted for heterogeneity to develop an overall ranking of countries on the closeness of their government to the people. The resulting index is associated with higher level of human development and lower level of corruption, and thus provides a useful explanation of the Arab Spring and other recent political movements and waves of dissatisfaction with governance around the world.
Keywords: H10; H11; H83; I31; O10; 330; localization; decentralization; home rule; fiscal autonomy; political autonomy; administrative autonomy; local governance; government accountability; trust in government; good governance; responsive; accountable and fair governance